Beginning english writing skills a handbook with practice - Scheraga, Mona (National Textbook Company, a division of NTC/Contemporary Publishing Group, Inc, 1998)
Provides instruction in basic writing skills for adult and young adult students, describing various types of writing, such as notes and messages, forms, letters and mail orders, academic and on-the-job writing, and including a vocabulary list, examples, and exercises for each style